Pre-Eid Grave Visitation (Munjung) as a Living Tradition: The Perspective of ‘Urf and Maqasid Shari’ah in Gayamdompo Village, Karanganyar Regency - Sri Wahyuni; Nabila Aulya Brilianfineza; Qodim Ma’shum (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This research aims to examine the pre-Eid munjung tradition as a living tradition of the Muslim community in Gayamdompo Village, Karanganyar, from the perspective of 'urf and maqasid syari'ah. The research employs a qualitative approach with field research methods. Data were obtained thru interviews, observations, and documentation. The research results show that the munjung tradition, which involves giving gifts to family, relatives, and neighbors before Idulfitri, is still preserved from generation to generation. This tradition is interpreted as a form of respect for parents, strengthening of family ties, and social solidarity within the community. In the perspective of 'urf, the munjung tradition is considered 'urf shahih because it has become a habit accepted by the community and does not contradict Islamic law. Meanwhile, from the perspective of maqasid syari'ah, the munjung tradition contains values of benefit, especially in maintaining family relationships, strengthening brotherhood, and fostering a spirit of sharing. This research shows that local traditions can have legitimacy in Islamic law as long as they are beneficial and do not contradict the principles of sharia.